ROLE OF PRIMARY HEALTH CARE IN THE MANAGEMENT AND CONTROL OF OBESITY - Siega Nepomuceno, Matheus; Lima Silva de Abreu, Letícia; Fonseca Almeida, Fernandez; Alves Moraes Nogueira, Edila; Barros Pinheiro, Rafaela; Alencar Fróes, Kênia; Pimenta Faria Galvão, Carolliny; Paiva Santos Rocha, Silvânia; Caroline Pereira Costa, Ana; Ferreira Santana, Flávia; Vieira de Oliveira, Valdira; Scremin, Marlete; et al. (Health and Society, 2026)
The aim was to describe the role of primary health care in the attention to and control of obesity. An integrative literature review study was conducted. The descriptor obesity and primary care was used to search the databases Scientific Electronic Library Online, Latin American and Caribbean Health Sciences Literature, and Virtual Health Library; books and manuals from the Ministry of Health regarding the subject of study were also considered. The approach to obese patients is often permeated by stigma, over-medicalization, and excessive screenings not based on evidence. Three main practices were identified as strategies for caring for obese patients in primary health care, which are: not prescribing weight-loss medications in isolation without a robust therapeutic program including diet, physical activity, and behavioral change; not prescribing weight-loss medications for individuals with mild obesity without comorbidities; and not failing to perform evaluation and follow-up with a multidisciplinary team, including a nutritionist and psychologist, for obese individuals. Significant practices have been identified that can be carried out by professionals during the care of users with obesity, which can reverse the logic of excessive screening, requests for additional tests, overmedicalization, and stigmatization.